sje20131006 - Nils Martin Sjaggo; Brita Stina Sjaggo; Ann-Charlotte Sjaggo; Joshua Karl Wilbur (Joshua Wilbur, 2013)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) Martin discusses the location (Säjjdegávva) with Ann-Charlotte; Martin plays with his granddaughter. Martin describes various sheds on his property.